The Use of Blood Flour as a Substitute for Fish Meal in Feed of BEST Nile Tilapia (Oreochromis niloticus) - supriadi, feri; rosmawati, rosmawati; kurniasih, titin (Jurnal Mina Sains, 2018)
This research was aimed to determine the optimum level of inclusion of blood flour in feed formulaton of Nile Tilapia as a substitute for fish meal. The materials of this research are a feed and Nile Tilapia with an average weight of 17 g of a total of 120 fingerling. The experiment design has been conducted  were completely random design with 5 treatments and 3 replications. The treatments are the substitution of fish meal with the blood flour of  0%, 25%, 50%, 75%, and 100%. Spesific growth rate, the mount of feed consumption, food efficiency,  survival rate, and water quality has been evaluated.  The results of research showed that spesific growth rate  and food efficiency were significantly different between treatments (P<0.05), and the highest of spesific growth rate  and food efficiency there are on treatment D (the substitution of fish meal with the blood flour of 75%) each 1.75% and 63.45%. The lowest of spesific growth rate  and food efficiency there are on treatment A (the substitution of fish meal with the blood flour of  0%) each 1.42% and 48.98%. The blood fluor as a substitution of fish meal in artificial feed for Nile Tilapia can substitute the fish meal of 100% with level of inclusion of  9% in feed formulation. The combination between the blood fluor and fish meal give the best of  growth performance and feed efficiency. Key words: Nile Tilapia, feed efficiency, survival rate, growth rate